Taxonomic note on Eupithecia cupressata Pearsall (Lepidoptera: Geometridae: Eupitheciini) - Ferris, Clifford D. (Zootaxa, 2006)
The male of Eupithecia cupressata Pearsall is described, and illustrations of adults and genitalia of both sexes are provided.